2016
DOI: 10.1002/mma.3814
|View full text |Cite
|
Sign up to set email alerts
|

Data mining algorithms to compute mixed concepts with negative attributes: an application to breast cancer data analysis

Abstract: In the design of mathematical methods for a medical problem, one of the kernel issues is the identification of symptoms and measures that could help in the diagnosis. Discovering connections among them constitute a big challenge because it allows to reduce the number of parameters to be considered in the mathematical model. In this work, we focus on formal concept analysis as a very promising technique to address this problem. In previous works, we have studied the use of formal concept analysis to manage attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…They will be A C C E P T E D M A N U S C R I P T inspired by the classical ones but take into account the advantages provided by the algebraic results presented here, allowing an increase in performance. As a first step in this direction, in [20], we make a review of the most relevant traditional algorithm for mining concept lattices and propose a preliminary extended versions of all of them to compute mixed concept lattices. Our intention is to study the applicability of the results given in [1] to the problem of mining mixed concept lattices.…”
Section: Discussionmentioning
confidence: 99%
“…They will be A C C E P T E D M A N U S C R I P T inspired by the classical ones but take into account the advantages provided by the algebraic results presented here, allowing an increase in performance. As a first step in this direction, in [20], we make a review of the most relevant traditional algorithm for mining concept lattices and propose a preliminary extended versions of all of them to compute mixed concept lattices. Our intention is to study the applicability of the results given in [1] to the problem of mining mixed concept lattices.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the literature, it is noticeable that different techniques got the highest accuracy in each study as follows: in the study conducted by [11], the highest accuracy was achieved by Bayes Network (BN), and SVM and DT (C5.0) got the best accuracy in [12]. Similarly, by looking at [13], it is noticeable that the highest accuracy was yielded by LR and in [15] the highest accuracy was achieved by the J48 classifier.…”
Section: Related Workmentioning
confidence: 99%
“…To analyze breast cancer data, [15] utilized four different DT classification algorithms, namely, Classification and Regression Trees (CART), J48, Best First Tree (BF Tree) and DT (AD Tree). The experiment employed the WEKA tool, and the results demonstrated that the J48 classifier reached the highest accuracy of 99% whereas the CART algorithms resulted in 96% accuracy; AD Tree algorithm resulted in 97%, and BF Tree algorithm resulted in 98%.…”
Section: Related Workmentioning
confidence: 99%
“…[3] have approached the generation of mixed implications from two given sets of implications only with positive and negative attributes respectively. We have followed this line: in [7], we extended the classical FCA framework with new derivation operators constituting a Galois connection for the treatment of negative and positive information in FCA and in [5,6] we proposed some mining algorithms to derive directly mixed implications.…”
Section: Summary Of the Workmentioning
confidence: 99%